Features of change of mechanical properties of precipitation hardening alloy 47ХНМ at hardening and ageing; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Mukazhanov E. B.; Skakov M. K.; Isaeva Zh. M.; Erbolatuly D. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа